Upaya mediasi non-litigasi dalam penyelesaian konflik pembagian harta waris sama rata: Studi Kasus di Desa Grogol Kecamatan Gondangwetan Kabupaten Pasuruan - Khoiriyah, Inayatul (Maliki Interdisciplinary Journal, 2025)
The division of inheritance often causes conflict in society, especially when it is done not in accordance with the provisions of Islamic law that stipulate a 2:1 ratio of parts between boys and girls. This study aims to examine the effectiveness of non-litigation mediation efforts in resolving The Division of inheritance distribution conflicts equally in Grogol Village, Gondangwetan District, Pasuruan Regency. This study uses a qualitative method with a case study approach, through interviews, observations, and documentation as a data collection technique. The results of the study show that non-litigation mediation facilitated by a religious leader with a settlement mediation approach is able to bridge the interests of both parties. Although the mediation process was at an impasse, the personal approach and caucus system used by the mediator managed to ease tensions and open up room for compromise. The final agreement was reached while still taking into account the values of Islamic law and social justice in the family. These findings prove that non-litigation mediation is an effective, efficient, and relevant alternative to dispute resolution in the social and cultural context of society. The success of mediation depends heavily on the skill of the mediator, the willingness of the parties, and the strength of deep-rooted local values.